2009
DOI: 10.1128/aem.02738-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Concentration on the Growth Rate of Pseudomonas syringae and the Expression of Virulence Factors in hrp -Inducing Minimal Medium

Abstract: Although chemically defined media have been developed and widely used to study the expression of virulence factors in the model plant pathogen Pseudomonas syringae, it has been difficult to link specific medium components to the induction response. Using a chemostat system, we found that iron is the limiting nutrient for growth in the standard hrp-inducing minimal medium and plays an important role in inducing several virulence-related genes in Pseudomonas syringae pv. tomato DC3000. With various concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 25 publications
(35 reference statements)
1
41
0
Order By: Relevance
“…It was expected that abundant iron would repress high-affinity iron scavenging, but the induction of virulence genes was surprising. In a follow-up study, Kim et al found that expression of virulence factors in hrp-inducing minimal medium was limited by iron availability and that higher iron to well above 10 M continued to induce higher virulence gene expression (32,33). Taken together, these results indicate not only that the environment in which DC3000 causes disease is relatively iron rich, but also that iron-as opposed to the lack of it-may act as a signal for DC3000 pathogenesis.…”
mentioning
confidence: 53%
“…It was expected that abundant iron would repress high-affinity iron scavenging, but the induction of virulence genes was surprising. In a follow-up study, Kim et al found that expression of virulence factors in hrp-inducing minimal medium was limited by iron availability and that higher iron to well above 10 M continued to induce higher virulence gene expression (32,33). Taken together, these results indicate not only that the environment in which DC3000 causes disease is relatively iron rich, but also that iron-as opposed to the lack of it-may act as a signal for DC3000 pathogenesis.…”
mentioning
confidence: 53%
“…The time points chosen for virulence gene expression are based on published reports (Vasil and Ochsner, 1999;Kim et al, 2009).…”
Section: Bacterial and Fungal Growth Conditions And Disease Assaysmentioning
confidence: 99%
“…The direct effect of IAA-Asp on the growth and expression of virulence genes of Pst DC3000 in vitro was studied as previously described (Vasil and Ochsner, 1999;Kim et al, 2009). The time points chosen for virulence gene expression are based on published reports (Vasil and Ochsner, 1999;Kim et al, 2009).…”
Section: Bacterial and Fungal Growth Conditions And Disease Assaysmentioning
confidence: 99%
“…To measure PME activity, plants were inoculated with bacteria or mock (5 mM MgSO 4 ) and three leaves from one plant were collected at the indicated time points per biological replicate. To measure PME activity in culture grown bacteria, Pma ES4326 was grown overnight at room temperature in either King's B or hypersensitive response and pathogenicityinducing minimal medium (Kim et al, 2009) using 0.2% Fru as a carbon source.…”
Section: Pathogen Strains Growth Conditions and Pathogen Growth Assaysmentioning
confidence: 99%